The impact of international financial institutions on small and medium enterprises: The case of EIB lending in Central and Eastern Europe - Áron Gereben; Anton Rop; Matic Petriček; Adalbert Winkler (European Investment Bank (EIB), 2019)
Does IFI funding provide support to SMEs receiving such funding? We assess the impact of funding by the European Investment Bank (EIB) on the performance of 5,223 SMEs in eight countries of Central and Eastern Europe (CEE) during 2008-2014. Our results, derived from propensity score matching and difference-in-difference estimation exercises, indicate that EIB lending has a positive effect on employment, revenues and profitability. This positive effect holds irrespective of the economy entering a prolonged crisis or a seeing a recovery in the years following EIB funding. Overall, our results provide support to the view that IFI funding makes a difference in a period characterized by financial and economic turmoil.
Keywords: G01; H81; L25; 330; International financial institutions; SMEs; impact; financial crisis